Managing Migration: The Global Challenge. - Martin, Philip; Zürcher, Gottfried (Population Bulletin, 2008)
The quantity of international migrants has hit an all-time high. In 2005, the world's migrants numbered 191 million, meaning that 3 percent of the global population left their country of birth or citizenship for a year or more. Those who migrate usually do so to a nearby country, with the largest flow of migrants being from less developed to better developed countries. However, almost as many people move from one developing country to another, and a lot of people also move from one industrialized nation to another. The flows from developed to less developed countries are much smaller. The international community believes that international migration should be voluntary, but the right to emigrate is stronger than the right to immigrate, and most countries attach conditions to immigration. The global challenge of managing migration is explored in a detailed report.